NREGA: An effective way to fight poverty - Dr. Raj Bihari Lal Srivastava (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
Public works programs, aimed at building a strong social safety net through redistribution of wealth and generation of meaningful employment, are becoming increasingly popular in developing countries. The National Rural Employment Guarantee Act (NREGA), enacted in August 2005, is one such program in India. This paper assesses causal impacts (Intent-to Treat) of NREGA on public works participation, labor force participation, and real wages of casual workers by exploiting its phased implementation across Indian districts. Using nationally representative data from Indian National Sample Surveys (NSS) and Difference-in Difference framework, we find that there is a strong gender dimension to the impacts of NREGA: it has a positive impact on the labor force participation and this impact is mainly driven by a much sharper impact on female labor force participation. Similarly, NREGA has a significant positive impact on the wages of female casual workers-real wages of female casual workers increased 8% more in NREGA districts compared with the increase experienced in non-NREGA districts. However, the impact of NREGA on wages of casual male workers has only been marginal (about 1%). Using data from pre-NREGA period, we also perform falsification exercise to demonstrate that the main conclusions are not confounded by pre-existing differential trends between NREGA and non-NREGA districts.